2018
DOI: 10.1186/s40580-018-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cellular gene expression by nanomaterials

Abstract: Within a cell there are several mechanisms to regulate gene expression during cellular metabolism, growth, and differentiation. If these do not work properly, the cells will die or develop abnormally and, in some cases, even develop into tumors. Thus, a variety of exogenous and endogenous approaches have been developed that act on essential stages of transcription and translation by affecting the regulation of gene expression in an intended manner. To date, some anticancer strategies have focused on targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Importantly, this observed regulation may also be caused by epigenetic modifications, 96 such as alteration of DNA methylation and histone modifications, thereby affecting how genes are turned on or off, subsequently modulating the expression of genes involved in plant growth and development. For example, it has been shown that cadmium telluride quantum dots and silica NPs affect the global DNA methylation pattern, modulate DNA methyltransferase activity, methyl-CpG-binding domain (MBD) protein expression, and/or alter posttranslational modifications of histone proteins; 97 similar activity with nano-sulfur may be possible.…”
Section: Mechanisms Of Nano-sulfur Beneficial Impact On Plantsmentioning
confidence: 99%
“…Importantly, this observed regulation may also be caused by epigenetic modifications, 96 such as alteration of DNA methylation and histone modifications, thereby affecting how genes are turned on or off, subsequently modulating the expression of genes involved in plant growth and development. For example, it has been shown that cadmium telluride quantum dots and silica NPs affect the global DNA methylation pattern, modulate DNA methyltransferase activity, methyl-CpG-binding domain (MBD) protein expression, and/or alter posttranslational modifications of histone proteins; 97 similar activity with nano-sulfur may be possible.…”
Section: Mechanisms Of Nano-sulfur Beneficial Impact On Plantsmentioning
confidence: 99%
“…MNPs can be used to remotely monitor different molecules and processes at the nanoscale level under low-frequency magnetic field exposure. In particular, they are proposed to be applied for the separation and purification of biological molecules and cells [4], as well as for gene expression regulation and the activation of various signaling cascades in the cell [5]. Additionally, in cancer therapy MNPs can act as drug carriers, facilitating their accumulation and release in the tumor under an external magnetic field exposure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main directions of modern nanotechnology is the elaboration of the methods to synthesize and investigate physical-chemical and biological properties of nanosized materials (Chun et al, 2018;Gupta & Xie, 2018;Zhang, 2018). In particular, these investigations are related to nanoparticles (NPs) of metal oxides, especially titanium dioxide (ТіО 2 ) and zinc oxide (ZnO), widely used in various branches of industry, including biosensorics, biotechnologies, pharmacology, cosmetology, etc.…”
Section: Introductionmentioning
confidence: 99%